2010
DOI: 10.1021/bi902211w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phosphorylation in the Motor Domain of Human Myosin IIIA on Its ATP Hydrolysis Cycle

Abstract: Previous findings suggested that the motor activity of human myosin IIIA (HM3A) is influenced by phosphorylation [Kambara, T., et al. (2006) J. Biol. Chem. 281, 37291–37301]; however, how phosphorylation controls the motor activity of HM3A is obscure. In this study, we clarify the kinetic basis of the effect of phosphorylation on the ATP hydrolysis cycle of the motor domain of HM3A (huM3AMD). The affinity of human myosin IIIA for filamentous actin in the presence of ATP is more than 100-fold decreased by phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…They report that the motor-only construct exhibits an extremely high affinity for actin, suggesting that this construct behaves very differently than the construct in our studies. The kinetic analysis of this motor-only construct following phosphorylation with an external kinase domain resulted in a 100-fold reduction in actin affinity of the motor (3,12). The maximal ATPase results of two reports from the same group (2,3,12) are contradictory, as the earlier study reported a 3-fold lower maximal rate in the dephosphorylated state, whereas the more recent report suggests no change.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…They report that the motor-only construct exhibits an extremely high affinity for actin, suggesting that this construct behaves very differently than the construct in our studies. The kinetic analysis of this motor-only construct following phosphorylation with an external kinase domain resulted in a 100-fold reduction in actin affinity of the motor (3,12). The maximal ATPase results of two reports from the same group (2,3,12) are contradictory, as the earlier study reported a 3-fold lower maximal rate in the dephosphorylated state, whereas the more recent report suggests no change.…”
Section: Discussionmentioning
confidence: 82%
“…The Ikebe group (3,12) has reported the kinetic analysis of a motor-only human Myo3A construct with both the kinase and neck domains removed. They report that the motor-only construct exhibits an extremely high affinity for actin, suggesting that this construct behaves very differently than the construct in our studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The functions of kinase/myosins are of interest because of their importance for sensory cell function and survival. The kinase/myosins of vertebrates are molecular motors, and the motor and actin binding properties of human MYO3A are being studied in detail (Komaba et al. 2003, 2010; Kambara et al.…”
mentioning
confidence: 99%